Determination of Heavy Metal Contents in Milk Samples: A Review - Pari Condori, Guilmer Rony; Quisocala Herrera, Jhimmy Alberth (Walisongo Journal of Chemistry, 2023)
In the dairy industry, mining is the main industry that affects the production of this food and its dairy products, with the contamination of heavy metals such as lead (pb), cadmium (cd) and mercury (Hg), a investigation of the different scientific articles, the purpose of this article is to present the different methods used to determine the concentrations of contaminants, such as the use of atomic absorption spectrometry in cow's milk, the method in this investigation begins with the collection of information from the bibliographic database of abstracts and citations of scientific articles Scopus, the selection of scientific production, working with fifty (50) scientific articles, with a maximum age of five (5) years having a subject in common, about the contamination of milk and dairy products, mass spectrometry to determine the level of contamination produced in milk , result that the concentrations of heavy metals such as lead, cadmium and mercury exceed in all the samples analyzed, the FDA recommended permissible limits mainly that are greater than 0.020 mg / kg.